Effectiveness of temozolomide combined with whole brain radiotherapy for non‐small cell lung cancer brain metastases - Zhu, Ying (Thorac Cancer, 2018)
BACKGROUND: We performed a retrospective analysis to compare the efficacy of whole brain radiotherapy (WBRT) combined with temozolomide (TMZ) versus WBRT alone as first‐line treatment for brain metastases (BM). METHODS: Seventy‐eight non‐small cell lung cancer patients with BM were observed, including 45 patients who received WBRT plus TMZ (TMZ + WBRT) and 33 patients who received WBRT alone (WBRT). The primary outcome was overall survival (OS). Secondary outcomes included progression‐free survival (PFS), objective response rate (ORR), and adverse events. RESULTS: The TMZ + WBRT arm achieved significant improvement in ORR (P = 0.0108) compared to the WBRT arm. PFS in the TMZ + WBRT arm was significantly longer than in the RT arm (6.0 vs. 3.5 months; P = 0.038). OS was not significantly different between the two arms. Although increased adverse reactions were experienced in the TMZ + WBRT arm, patients were tolerant of the side effects. Statistically significant differences in neurocognitive function and quality of life were observed between the arms at six months. CONCLUSION: Concomitant TMZ + WBRT compared to WBRT alone significantly increases ORR and median PFS in patients with BM, but no remarkable difference in median OS was found. Adding TMZ to the treatment strategy could prevent neurocognitive function and quality of life from deteriorating. Although the addition of TMZ increases the incidence of adverse effects, no significant difference was observed. Thus, TMZ is safe and effective.